Kajian Kajian Standing Stock Ikan Lemuru (Sardinella lemuru) di Perairan Selat Bali Menggunakan Metode Hidroakustik - Pratama, I Gede Merta Yoga; Putri, Mutiara Rachmat; Setiawan, Agus (Journal of Marine and Aquatic Sciences; Vol 9 No 2 (2023), 2024)
The Bali Strait area contains various fishery resources, one of which is Sardinella lemuru . Nevertheless, the community struggles to apply technology to estimate the biomass of Lemuru in the water column. This research aims to estimate the biomass of Lemuru using hydroacoustic method in Bali Strait. The primary data for this research was taken in 3 fish-catching trips in Bali Strait area, involving the traditional fishermen in Badung Regency. The relevant data for this research are: acoustic data collected by BlueRobotics Ping Sonar Altimeter and Echosounder. The processed data were quantitatively analyzed by its Target Strength (TS) and the estimation of fish length, weight, and density. The data validation was done by comparing the acoustic data calculation result to the 120 fish samples measured after being caught. This research resulted that, from the 3 catching trips of Lemuru in Bali Strait area, the Target Strength (TS) being in the range of -49.5 dB to -40.5 dB; the estimated fish length (L) of 7,94 cm to 22,4 cm; and the estimated fish weight of 5 grams to 112 grams. There were 13,823 fishes detected by the sensor with the average density of 4.100 ind/1.000m 3 . The total estimated biomass of Lemuru among the 3 trips is 1.040 kg in the water area of 7,3 km 2 , hence 142 kg/km 2 .